Baylis-Hillman derived benzopyrans and related systems : a synthetic and mechanistic study - Robinson, Ross Stuart (Rhodes University, Faculty of Science, Department of Chemistry, 1998)
The Baylis-Hillman reaction between substituted salicylaldehydes and various acrylate species has been shown to afford complex reaction mixtures, careful chromatography of which has led to the isolation of an extensive range of novel compounds. One- and two-dimensional NMR spectroscopic, mass spectrometric and X-ray crystallographic analysis of these compounds have permitted identification of no less than eight general classes of chromene and coumarin derivatives. The formation of the various product types is attributed to cascades of successive reactions stemming, in each case, from a Baylis-Hillman product as the common intermediate. The mechanistic sequence involved in the formation of the various chromene and coumarin derivatives have been elucidated by examining isolated or specifically prepared compounds as putative reaction intermediates. Conjugate addition and acyl or allylic substitution by various nucleophiles appear to be common processes in the formation of the chromene and coumarin derivatives, and studies focussing on these processes have been undertaken. Reactions of Baylis-Hillman adducts have been carried out, using oxygen, sulfur and nitrogen nucleophiles, in order to explore stereoselectivity and regioselectivity trends. The results show that the reactions proceed with a very high degree of regioselectivity, affording conjugate addition rather than acyl substitution products. The diastereoselectivity observed for the addition products, however was typically low. A kinetic study to explore the regioselectivity of the reaction between various Baylis-Hillman derived halogeno esters and the nucleophile, methyl 3-oxobutanolate enloate, in two different base-solvent systems at high dilution was also undertaken. The reactions were monitored by Â¹H NMR spectroscopy, and the results revealed that the reaction kinetics are more complex than originally anticipated. A mechanistic rationalisation is offered which is consistent with both the kinetic data and the observed regioselectivity trends.
Keywords: Benzopyrans; Coumarins; Heterocyclic compounds -- Derivatives